2018
DOI: 10.14393/rbcv70n4-46139
|View full text |Cite
|
Sign up to set email alerts
|

Shallow landslide susceptibility assessment using SINMAP in Nova Friburgo (Rio de Janeiro, Brazil)

Abstract: Landslides cause enormous economic damage and fatalities worldwide. The "Mega disaster" in the mountainous region of Rio de Janeiro took place on 11 th and 12 th January 2011 and impacted seven municipalities. These landslide events are considered the worst disasters in Brazilian history. Landslide susceptibility zonation is one of the most important tasks in landslide risk assessment. The different approaches for landslide susceptibility modelling include: 1) Heuristics; 2) Statistical and; 3) Deterministic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…They Several studies have used the advanced model Sinmap in different study areas. Reference [57] used the Sinmap to study the municipality of Nova Friburgo-RJ, Brazil, located in the mountainous area of Serra do Mar. It is a steep slope area with a declivity ranging from 15˚ to more than 35˚ degrees.…”
Section: Sinmap Modelmentioning
confidence: 99%
“…They Several studies have used the advanced model Sinmap in different study areas. Reference [57] used the Sinmap to study the municipality of Nova Friburgo-RJ, Brazil, located in the mountainous area of Serra do Mar. It is a steep slope area with a declivity ranging from 15˚ to more than 35˚ degrees.…”
Section: Sinmap Modelmentioning
confidence: 99%
“…A deep study about loss of life due to the 2011 landslides at the Nova Friburgo municipality revealed that cause of death for all the victims was mechanical asphyxia by burial. A total number of landslide-related deaths was 434 (205 women and 228 men) (Cardozo et al, 2017;2018). This represents more than 47% of fatalities in the Mega-disaster occurred at the mountainous region of Rio de Janeiro.…”
Section: Social Vulnerability and The 2011 Landslide-related Fatalitiesmentioning
confidence: 99%
“…Today, this model is used for landslide zoning of the catchments by GIS. Practically this model examines the stability of each pixel separately (Pack et al, 2001;Michel et al, 2014;Cardozo et al, 2018;Sabzevari and Talebi, 2021).…”
mentioning
confidence: 99%